Review of sheep and goat pox disease: current updates on epidemiology, diagnosis, prevention and control measures in Ethiopia - Girma Zewdie (BMC, 2021)
Abstract Sheep pox, goat pox, and lumpy skin diseases are economically significant and contagious viral diseases of sheep, goats and cattle, respectively, caused by the genus Capripoxvirus (CaPV) of the family Poxviridae. Currently, CaPV infection of small ruminants (sheep and goats) has been distributed widely and are prevalent in Central Africa, the Middle East, Europe and Asia. This disease poses challenges to food production and distribution, affecting rural livelihoods in most African countries, including Ethiopia. Transmission occurs mainly by direct or indirect contact with infected animals. They cause high morbidity (75-100% in endemic areas) and mortality (10-85%). Additionally, the mortality rate can approach 100% in susceptible animals. Diagnosis largely relies on clinical symptoms, confirmed by laboratory testing using real-time PCR, electron microscopy, virus isolation, serology and histology. Control and eradication of sheep pox virus (SPPV), goat pox virus (GTPV), and lumpy skin disease (LSDV) depend on timely recognition of disease eruption, vector control, and movement restriction. To date, attenuated vaccines originating from KSGPV O-180 strains are effective and widely used in Ethiopia to control CaPV throughout the country. This vaccine strain is clinically safe to control CaPV in small ruminants but not in cattle which may be associated with insufficient vaccination coverage and the production of low-quality vaccines.